?TERNARY LIQUID EQUILIBRIA OF ETHANOL-WATER-OLEYL ALCOHOL AND ETHA- NOL-WATER-OLEIC ACID SYSTEMS (Biological Sciences - PJSIR, 2003)
The ternary equilibrium data are presented for the ethanol -water - oleyl alcohol and ethanol- water - oleic acid systems at 30°C. The binodal curves, tie lines, plait points, distribution coefficients and separation factors have been determined to extract ethanol from the aqueous solution. Hand’s method has been used to correlate tie lines and to calculate coordinates of plait points. Tie line data were satisfactorily correlated by the Othmer - Tobias method on a mass fraction basis.